Window film and method of manufacturing a front window with window film
Patent Information
- Application Number
- CN202580023905.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2025-03-24
- Publication Date
- 2026-10-27
AI Technical Summary
[0018]根据本发明,能够提供窗膜及带窗膜的前窗的制造方法,所述窗膜抑制树脂膜在形成硬涂层时产生褶皱,能够在贴附时追随被粘物的形状,隔热性高。
Smart Images

Figure CN122995945A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to window film and a method for manufacturing a front window with window film. Background Technology
[0002] Window film is a film applied to windows of moving objects such as cars and buildings to provide them with specific functions, and it is widely used.
[0003] Window films typically use resin films as the substrate. Resin films generally tend to have low hardness, resulting in poor scratch resistance and weather resistance.
[0004] Therefore, in addition to resin films, window films often have hard coatings that offer superior hardness, scratch resistance, and weather resistance compared to resin films. Hard coatings are primarily obtained by applying a composition used to form the hard coating onto a resin film and then allowing it to cure.
[0005] In addition, window film is sometimes applied to curved windows such as car windows. When a flat window film is applied to a curved surface, excess film is left, and the film tends to become loose, which can be one of the reasons for wrinkles after application.
[0006] Patent document 1 describes a window film that, by setting the heat shrinkage rate of the substrate and the hard coating within a specified range, can appropriately prevent the formation of scratches and wrinkles when pasted onto the object. Existing technical documents Patent documents
[0007] Patent Document 1: Japanese Patent Application Publication No. 2019-171781 Summary of the Invention (a) Technical problems to be solved
[0008] Patent Document 1 describes a method in which the thermal shrinkage rates of two orthogonal directions in the substrate are preferably set within a specified range, i.e., the thermal shrinkage rates of the two orthogonal directions are set to the same level. However, after in-depth research, the inventors of this application discovered that when the thermal shrinkage rates of the two orthogonal directions in the substrate are set to the same level, especially when the window film is attached to a large, curved object, the window film cannot fully follow the shape of the object and is prone to wrinkles.
[0009] Furthermore, the inventors of this application have discovered that when an infrared absorber is included in the composition for forming the hard coating to impart heat insulation to the window film, heat is generated during the formation of the hard coating. If this heat generation occurs, the resin film near the hard coating forming composition will thermally shrink, resulting in wrinkles in the resin film after the hard coating is formed. In other words, the formation of wrinkles in the resin film due to the hard coating results in a poor appearance of the manufactured window film.
[0010] The present invention was carried out in view of this actual situation, and aims to provide a window film and a method for manufacturing a front window with the window film, wherein the window film inhibits wrinkles in the resin film during the formation of a hard coating, can follow the shape of the object being adhered to during application, and has high heat insulation properties. (II) Technical Solution
[0011] The solution of the present invention is as follows.
[0012] [1] A window film having a resin film and a hard coating disposed on a main surface of the resin film, wherein, For a resin film heated and held at 180°C for 5 minutes, when the shrinkage rate in the MD direction before and after heating is set as A% and the shrinkage rate in the CD direction before and after heating is set as B%, A-B is greater than 0.4%. The hard coating contains indium tin oxide.
[0013] [2] The window film as described in [1], wherein the shrinkage rate in the MD direction is 0.75% or more.
[0014] [3] The window film as described in [1] or [2], wherein the visible light transmittance of the window film is 80% or more.
[0015] [4] The window film as described in any one of [1] to [3], wherein the near-infrared transmittance of the window film is less than 20%.
[0016] [5] The window film as described in any one of [1] to [4], wherein the window film is used for the front window of the moving body.
[0017] [6] A method for manufacturing a front window with a window film, comprising the following steps: attaching the window film described in [5] to the front window in such a way that the MD direction of the resin film is aligned with the long side direction of the front window. (III) Beneficial Effects
[0018] According to the present invention, a method for manufacturing a window film and a front window with the window film is provided, wherein the window film inhibits wrinkles in the resin film during the formation of a hard coating, can follow the shape of the object being adhered to during application, and has high heat insulation properties. Attached Figure Description
[0019] Figure 1A A cross-sectional schematic diagram illustrating an example of the window film of this embodiment. Figure 1B A cross-sectional schematic diagram is provided to illustrate other examples of the window film of this embodiment. Detailed Implementation
[0020] The present invention will now be described in detail based on specific implementation schemes.
[0021] (1. Window film) Window films, for example, have a substrate made of resin film and a hard coating with a higher hardness than the substrate.
[0022] To impart heat insulation properties to window films, the hard coating layer contains an infrared absorber. The hard coating layer is obtained by applying a composition for forming the hard coating onto a resin film during window film manufacturing, and then curing it, for example, by irradiating it with ultraviolet light. At this time, the light source used for irradiation emits light not only at wavelengths belonging to ultraviolet light but also at wavelengths belonging to visible light. Therefore, if the hard coating layer contains an infrared absorber with a specified absorption rate in the visible light wavelength range, the infrared absorber will absorb visible light and generate heat. If this heat is generated in the hard coating layer, the heat is transferred to the resin film, causing the resin film to shrink. If the resin film shrinks, wrinkles will form, resulting in an unsightly appearance of the window film.
[0023] Furthermore, since window film is flat, if it is applied along the shape of a curved substrate, unattached portions will remain, causing the film to loosen. This loosening prevents the film from fully conforming to the substrate, resulting in an unsightly appearance. Therefore, it is preferable to heat the film to cause it to shrink in a specific direction when applying it to a curved substrate using the shrinkage of the resin film caused by heat, thereby improving its conformity to the substrate.
[0024] However, if a resin film with high heat shrinkage is used to improve conformability, the shrinkage of the resin film due to the heat generated by the aforementioned infrared absorber also increases. Therefore, if the shrinkage of the resin film is used to improve conformability to the adhered object, there is a problem of increased wrinkles in the resin film during the formation of the hard coating. In other words, it is difficult to simultaneously achieve both the conformability to the adhered object obtained by utilizing the shrinkage of the resin film and the reduction of resin film wrinkles during the manufacture of the window film.
[0025] In this embodiment, as described below, by containing a specific infrared absorber and controlling the physical properties of the resin film, it is possible to balance the conformability to the adhered object obtained by utilizing the shrinkage of the resin film with the reduction of resin film wrinkles during the manufacture of the window film. The constituent elements of the window film will be described in detail below.
[0026] like Figure 1A As shown, the window film 1 of this embodiment has a resin film 10 as a substrate and a hard coating 11.
[0027] Furthermore, the window film may have other constituent elements as long as the effects of the present invention can be achieved. That is, the window film may also have layers other than the substrate and the hard coating. For example, in order to securely fix the window film to the substrate (window), such as... Figure 1BAs shown, an adhesive layer 12 can be disposed on the main surface 10b of the resin film 10, which is opposite to the main surface 10a on which the hard coating 11 is formed. When the adhesive layer 12 is disposed, in order to protect the adhesive layer 12 until it is adhered to the object, a release tab (not shown) can also be disposed on the main surface 12a of the adhesive layer 12.
[0028] (1.1. Resin film) In this embodiment, the resin film is a material that provides rigidity to the window film and functions as a substrate that supports the hard coating.
[0029] Resin films are typically formed by stretching molten resin into a sheet. In this process, the direction in which the molten resin flows is defined as the MD (machine direction), and the direction orthogonal to the MD is defined as the CD (cross direction). The MD and CD directions tend to have different orientations of the molecular chains constituting the resin. As a result, the properties of resin films along the MD and CD directions sometimes differ. That is, the properties of resin films along the MD and CD directions can sometimes exhibit anisotropy.
[0030] Before and after heating, the shrinkage of the resin film in the MD direction of this embodiment differs from the shrinkage in the CD direction. First, when the predetermined length of the leading edge of the heated resin film in the MD direction is set to 100%, and the length of the resin film along the MD direction after holding at 180°C for 5 minutes is X%, the shrinkage rate due to heating ((100-X)%) is defined as the shrinkage rate (A%) in the MD direction. For example, if the length of the resin film along the MD direction after holding at 180°C for 5 minutes is 95%, the shrinkage rate in the MD direction is 5%. Similarly, when the predetermined length of the leading edge of the heated resin film in the CD direction is set to 100%, and the length of the resin film along the CD direction after holding at 180°C for 5 minutes is Y%, the shrinkage rate due to heating ((100-Y)%) is defined as the shrinkage rate (B%) in the CD direction.
[0031] In this embodiment, the difference (A-B) obtained by subtracting the shrinkage rate of the resin film in the CD direction from the shrinkage rate in the MD direction is 0.4% or more. That is, in the resin film of this embodiment, the shrinkage rate in the MD direction is greater than the shrinkage rate in the CD direction.
[0032] Because the shrinkage rate of the resin film exhibits anisotropy in both the MD and CD directions, heating can be used during window film installation to cause the resin film to shrink significantly in a specific direction. This makes the window film easier to conform to the shape of the substrate, improving its installability.
[0033] The difference between the shrinkage rate in the MD direction and the shrinkage rate in the CD direction (A-B) is preferably 0.6% or more, and more preferably 0.8% or more. From the perspective of the manufacturing conditions of the resin film and to further suppress wrinkles in the resin film during the formation of the hard coating, the upper limit of the difference between the shrinkage rate in the MD direction and the shrinkage rate in the CD direction (A-B) is preferably 10%, and more preferably 3%.
[0034] Furthermore, the shrinkage rate (A%) in the MD direction is preferably 0.75% or more, more preferably 1.5% or more, provided that the shrinkage rate difference described above is met. This makes it easier for the window film to conform to the shape of the substrate, further improving the workability of the window film. From the perspective of resin film manufacturing conditions and further suppressing wrinkles in the resin film during the formation of a hard coating, the upper limit of the shrinkage rate in the MD direction is preferably 10%, more preferably 4%.
[0035] As for the resin film, any resin film can be selected as long as the shrinkage rate in the MD direction and the shrinkage rate in the CD direction are within the above-mentioned range. Specifically, examples of such resin films include: films or laminates of these resin films made of polyester resins such as polyethylene terephthalate and polyethylene naphthalate; polyolefin resins such as polyethylene, polypropylene, poly4-methyl-1-pentene, and poly(1-butene); polyurethane resins; polycarbonate resins; polyvinyl chloride resins; polyethersulfone resins; polyethylene sulfide resins; styrene resins; acrylic resins; polyamide resins; cellulose resins such as cellulose acetate.
[0036] Among these resin films, films or laminates of polyolefin resins and polyester resins with excellent mechanical strength and economy are preferred. From the perspective of easily obtaining the above-mentioned physical properties, films or laminates of polyester resins are particularly preferred, among which polyethylene terephthalate films or laminates containing polyethylene terephthalate are preferred.
[0037] A metal layer can be formed on the resin film as long as the resin film meets the above-mentioned physical properties. By providing a metal layer on the resin film, the optical properties of the window film can be easily adjusted. The metal layer can be a layer containing metal or a layer composed only of metal. Examples of metals contained in the metal layer include: aluminum, gold, silver, copper, nickel, cobalt, chromium, tin, indium, etc.; alloys of these metals; or oxides of these metals. Examples of methods for forming the metal layer include vacuum evaporation, sputtering, etc. Metal layers tend to reflect infrared rays, but they also tend to reduce the light transmittance of the window film. Therefore, for example, in applications where high visibility of the outside of the window is required, such as when the window film is used as a front window of a moving vehicle, it is preferable not to form a metal layer on the resin film. Since the hard coating of the window film in this embodiment contains an infrared absorber, its heat insulation performance is still excellent even without forming a metal layer on the resin film.
[0038] To improve the adhesion between the substrate and the layer deposited on the resin film, surface treatments can be applied to one or both sides of the substrate using methods such as oxidation or texturing. Examples of oxidation methods include corona discharge treatment, wet chromic acid treatment, flame treatment, hot air treatment, and ozone / ultraviolet irradiation treatment. Examples of texturing methods include sandblasting and solvent treatment.
[0039] The thickness of the resin film is not particularly limited as long as it exhibits the specified rigidity; it can be appropriately set according to the intended use. In this embodiment, from the perspective of improving workability and suppressing the formation of wrinkles in the resin film during manufacturing, the thickness of the resin film is preferably 10-200 μm, more preferably 15-150 μm, and even more preferably 20-80 μm.
[0040] The window film of this embodiment may have multiple layers of substrate made of resin film. From the perspective of making it easier to control the shrinkage characteristics of the window film, it is preferable to have only one layer of substrate made of resin film.
[0041] (1.2. Hard coating) The hard coating of this embodiment exhibits superior hardness, scratch resistance, and weather resistance compared to resin films. The window film is applied to the substrate with the hard coating exposed to the outside. Therefore, even after application, resin films are less prone to scratches from external forces. Furthermore, it provides excellent impact resistance because it prevents external forces from being directly transmitted to the substrate (such as car windows or building windows). Moreover, even if the substrate breaks, it suppresses the scattering of debris, thus providing excellent anti-scattering properties. Therefore, it maintains the appearance of moving objects such as cars and buildings, and improves safety.
[0042] Hard coatings can also have functions other than hard coating properties. In this embodiment, the hard coating has heat insulation properties (infrared absorption) in order to impart heat insulation to the window film.
[0043] From the perspective of improving the surface hardness, scratch resistance, weather resistance and heat insulation of window film, the thickness of the hard coating is preferably 1~20μm, more preferably 3~15μm.
[0044] From the perspective of improving the surface hardness, scratch resistance, weather resistance, and heat insulation of window film, the preferred weight per unit area of the hard coating is 1~20g / m². 2 More preferably 3~15g / m 2 Further preferably 3~10g / m 2 .
[0045] The hard coating is preferably composed of a material capable of imparting the aforementioned hardness, scratch resistance, weather resistance, and thermal insulation properties. In this embodiment, the hard coating is preferably a cured product formed by curing a hard coating forming composition.
[0046] (1.2.1. Composition for forming hard coating) In this embodiment, from the perspective of productivity and ease of obtaining the desired scratch resistance, the hard coating forming composition Q is preferably curable by active energy rays, and particularly preferably curable by ultraviolet light.
[0047] Specifically, the hard coating forming composition Q preferably includes an active energy ray curable resin (a) and an infrared absorber (c), and more preferably includes an active energy ray curable resin (a), a photopolymerization initiator (b), and an infrared absorber (c).
[0048] (1.2.2. Resins that are cured by active energy rays (a)) There are no particular limitations on the active energy ray-curable resin, and it can be selected from conventionally known active energy ray-curable resins. Examples include active energy ray-curable monomers, oligomers, or compositions containing these components.
[0049] Examples of active energy ray-curable monomers include polyfunctional (meth)acrylates. Examples of active energy ray-curable oligomers include urethane (meth)acrylates, polyester (meth)acrylates, polyether (meth)acrylates, and organosilicon (meth)acrylates.
[0050] Examples of polyfunctional (meth)acrylates include: 1,4-butanediol dimethacrylate, 1,6-hexanediol dimethacrylate, neopentyl glycol dimethacrylate, ethylene glycol dimethacrylate, propylene glycol dimethacrylate, hexanediol dimethacrylate, trimethylolethane trimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol trimethacrylate, pentaerythritol tetramethacrylate, and other pentaerythritol polyfunctional (meth)acrylates; dipentaerythritol pentamethacrylate, dipentaerythritol hexamethacrylate, and other dipentaerythritol polyfunctional (meth)acrylates; glycerol trimethacrylate, triallyl (meth)acrylate, etc.
[0051] Among these multifunctional (meth)acrylates, pentaerythritol multifunctional (meth)acrylates or dipentaerythritol multifunctional (meth)acrylates are preferred because they can impart moderate hardness, scratch resistance, and weather resistance to hard coatings.
[0052] (1.2.3. Infrared absorber (c)) The infrared absorber (c) is preferably an infrared absorber with excellent near-infrared absorption properties.
[0053] In this embodiment, the infrared absorber (c) is indium tin oxide (ITO). ITO has a lower absorption rate in the visible light wavelength range than other infrared absorbers. Therefore, even when the ITO-containing hard coating forming composition Q is cured by irradiation with ultraviolet light, the heat generated by the ITO due to visible light absorption is minimal. As a result, less heat is transferred to the resin film, thus suppressing resin film shrinkage and the associated wrinkling. Furthermore, due to the low absorption of visible light, high thermal insulation properties are achieved while maintaining a high level of transparency in the window film.
[0054] The content of ITO in the hard coating forming composition Q is preferably 10 to 300 parts by weight, more preferably 20 to 250 parts by weight, and even more preferably 40 to 200 parts by weight, relative to 100 parts by weight of the active energy ray curable resin (a). This further suppresses the shrinkage of the resin film during hard coating formation, and the resulting window film exhibits high thermal insulation properties.
[0055] (1.2.4. Photopolymerization initiator(b)) When using ultraviolet light as an active energy ray to cure the hard coating forming composition Q, the hard coating forming composition Q preferably contains a photopolymerization initiator (b). By including a photopolymerization initiator, a hard coating can be formed efficiently when the hard coating forming composition Q is irradiated with ultraviolet light. Here, a photopolymerization initiator refers to a compound that generates free radical species upon irradiation by active energy rays such as ultraviolet light.
[0056] Examples of photopolymerization initiators include: benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin n-butyl ether, benzoin isobutyl ether, acetophenone, dimethylaminoacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropanoyl)benzyl]phenyl}-2-methylpropane-1-one, 1-hydroxycyclohexylphenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone (2-methyl-1-[4-(methylthio)phenyl ...]phenyl [yl]-2-morpholinopropan-1-one), 4-(2-hydroxyethoxy)phenyl-2-(hydroxy-2-propyl)one, benzophenone, p-phenylbenzophenone, 4,4-diethylaminobenzophenone, dichlorobenzophenone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 2-aminoanthraquinone, 2-methylthioxanthone, 2-ethylthioxanthone, 2-chlorothioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, benzoylayl dimethyl ketal, acetophenone dimethyl ketal, p-dimethylaminobenzoate, oligomeric [2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propane-1-one], etc. These photopolymerization initiators can be used alone or in combination of two or more.
[0057] The content of photopolymerization initiator (b) is preferably 1 to 30 parts by mass relative to 100 parts by mass of the active energy ray-curable resin (a), more preferably 2 to 20 parts by mass, and even more preferably 3 to 10 parts by mass. As a result, the obtained hard coating readily exhibits the desired surface hardness and scratch resistance.
[0058] (1.2.5. Other additives) Furthermore, without impairing the effects of the present invention, the hard coating forming composition Q may appropriately contain other additives. Examples of such other additives include: antioxidants, ultraviolet absorbers, antistatic agents, colorants, polymerization accelerators, polymerization inhibitors, leveling agents, plasticizers, antiviral agents, antibacterial agents, fillers, and diluents.
[0059] (1.3. Adhesive layer) In this embodiment, the window film preferably has an adhesive layer. By attaching the adhesive layer to the surface of the object to which it is to be adhered, the window film can be securely fixed. The adhesive layer is obtained by forming the following adhesive into a layer.
[0060] An adhesive layer can consist of a single layer or multiple layers. When an adhesive layer has multiple layers, these layers can be the same or different from each other, and there are no particular restrictions on the combination of these multiple layers.
[0061] The thickness of the adhesive layer can be 5 to 100 μm, preferably 7 to 70 μm, more preferably 10 to 50 μm, and even more preferably 10 to 40 μm. This makes it easier to achieve suitable adhesion.
[0062] The composition of the adhesive constituting the adhesive layer is not particularly limited. For example, it can be any of acrylic adhesives, polyester adhesives, polyurethane adhesives, rubber adhesives, or silicone adhesives. Furthermore, the adhesive can be any of emulsion-type, solvent-type, or solvent-free type. Moreover, the adhesive may or may not have a cross-linked structure.
[0063] When the adhesive composition is an acrylic adhesive with a crosslinked structure, the adhesive can be exemplified as an adhesive with a crosslinked structure obtained by crosslinking an adhesive composition containing a (meth)acrylate polymer with a crosslinking agent. Furthermore, in this specification, (meth)acrylic acid refers to both acrylic acid and methacrylic acid. In addition, "polymer" also includes the concept of "copolymer".
[0064] Examples of (meth)acrylate polymers include polymers containing units derived from alkyl (meth)acrylates and units derived from monomers having reactive functional groups within the molecule (monomers containing reactive functional groups) as monomer units.
[0065] Examples of alkyl (meth)acrylates include alkyl (meth)acrylates with 1 to 20 carbon atoms in the alkyl group. Examples of monomers containing reactive functional groups include monomers with an intramolecular hydroxyl group (hydroxyl-containing monomers) and monomers with an intramolecular carboxyl group (carboxyl-containing monomers).
[0066] As a crosslinking agent, a crosslinking agent that reacts with the reactive functional groups of (meth)acrylate polymers is preferred, and examples include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, and metal chelate-based crosslinking agents.
[0067] Adhesives may contain additives commonly used in adhesives, as needed. Examples of such additives include: ultraviolet absorbers, infrared absorbers, tackifiers, fillers, softeners, antioxidants, light stabilizers, colorants, modifiers, rust inhibitors, flame retardants, hydrolysis inhibitors, surface lubricants, corrosion inhibitors, heat stabilizers, lubricants, antistatic agents, polymerization inhibitors, catalysts, leveling agents, thickeners, dispersants, defoamers, surfactants, etc.
[0068] (1.4. Physical properties of window film) The window film of this embodiment preferably has the following physical properties.
[0069] The window film of this embodiment preferably has a light transmittance (visible light transmittance) of 80% or higher in the wavelength range of 380~780nm. This ensures sufficient transparency of the window film. As a result, visibility through the window with the film applied is improved. For example, when the window film is applied to the windows of automobiles, it allows for good visual identification of the outside environment, improving driving safety.
[0070] The visible light transmittance is preferably 82% or higher, more preferably 84% or higher. The upper limit of visible light transmittance can be 100%.
[0071] The window film of this embodiment preferably has a light transmittance (near-infrared transmittance) of 20% or less in the wavelength range of 780~2500nm. Therefore, the window film can provide good heat insulation, suppressing the rise in surface temperature of components inside buildings and automobiles, as well as the rise in temperature of the interior space. This low near-infrared transmittance is achieved by including an infrared absorber in the hard coating; however, the lower the near-infrared transmittance, the greater the heat generated during the formation of the hard coating. Therefore, in window films requiring such low near-infrared transmittance, using ITO as an infrared absorber to suppress heat generation is more important.
[0072] The near-infrared transmittance is preferably 18% or less, more preferably 16% or less. The lower limit for near-infrared transmittance can be 0%. The following can be used as guidelines for controlling near-infrared transmittance: The more infrared absorber contained in the hard coating, the lower the near-infrared transmittance tends to be. Furthermore, the greater the weight per unit area of the hard coating, the lower the near-infrared transmittance tends to be. Additionally, the smaller the particle size of the infrared absorber and the more uniformly it is dispersed in the hard coating, the lower the near-infrared transmittance tends to be.
[0073] Furthermore, the visible light transmittance and near-infrared transmittance of the aforementioned window film can be measured according to JIS S3107. Specific measurement methods will be described in the following examples.
[0074] (1.5. Manufacturing of window film) There are no particular limitations on the method for manufacturing the window film; any known method can be used. For example, a hard coating can be formed on one main surface of the resin film. Specifically, a coating liquid of the aforementioned hard coating forming composition Q is applied to one main surface of the resin film and then dried. The coating liquid of the hard coating forming composition Q can be prepared by mixing the components constituting the hard coating forming composition Q and using a known diluent as needed. Examples of methods for applying the coating liquid include: bar coating, knife coat method, roller coating, blade coat method, die coating, gravure coating, etc. The dried hard coating forming composition Q is cured by irradiating it with active energy rays such as ultraviolet light, thereby forming a hard coating on the resin film.
[0075] When ultraviolet light is used as an active energy ray for irradiation, known devices such as high-pressure mercury lamps, xenon lamps, and metal halide lamps can be used as ultraviolet irradiation devices.
[0076] When ultraviolet light is used as an active energy ray for irradiation, the illuminance is preferably 50~1000 mW / cm². 2 Around 100~500mW / cm², more preferably 100~500mW / cm² 2 The optimal light intensity is 25~2000 mJ / cm². 2 More preferably 50~1000mJ / cm 2 More preferably 70~500mJ / cm 2 .
[0077] When the window film has an adhesive layer, the adhesive layer can be obtained by applying a coating liquid of a composition (adhesive composition) for forming the adhesive layer to another main surface of a resin film without a hard coating, and then drying it. When the adhesive composition contains a crosslinking agent, an adhesive layer containing a crosslinked structure can also be obtained as needed by heating, curing, or otherwise modifying the adhesive composition.
[0078] (2. Uses of window film) The window film of this embodiment is applied to a substrate. The substrate is a window, such as the window of a moving object like a car, or the window of a building. In this embodiment, the substrate is preferably a window with a curved surface, more preferably a window with a large curvature or a window with a large change in curvature. An example of such a window is a car window. The car window can be a front window, a rear window, a side window, or a door window; a front window with a large area and a large curvature is preferred as the substrate.
[0079] In this embodiment, the window film is preferably shaped to fit the shape of the substrate before being applied to it. The method for shaping it to the specified shape can be any known method. For example, the window film can be temporarily applied to the substrate, pre-deformed to the shape of the substrate, and then cut or processed.
[0080] When applying the window film of this embodiment to the windshield of a car, it is preferable to align the MD direction of the resin film with the long side (vehicle width) of the windshield. Typically, the curvature of the windshield is greater at the ends and center along its long side, with a larger variation in curvature. However, the curvature remains almost unchanged along the short side (vehicle height). Therefore, if the window film is applied to the windshield, it is particularly prone to creating a slack section at the ends along the long side where the film cannot follow the windshield's contours. Applying the film to the windshield in this slack state can easily result in wrinkles, thus becoming an aesthetic problem.
[0081] When using the window film of this embodiment, as described above, wrinkles in the resin film of the window film before application are suppressed, and the difference between the shrinkage rate in the MD direction and the shrinkage rate in the CD direction is controlled within a specified range. Therefore, there are fewer wrinkles in the resin film before application, and even if the window film loosens during application, the loosened portion can be heated to cause the window film to shrink significantly in the MD direction, thereby fully following the front window. As a result, the window film can be given the specified heat insulation properties, and the formation of wrinkles after application is suppressed.
[0082] Thus, by using the window film of this embodiment, a front window with a window film can be obtained.
[0083] Furthermore, in this specification, when denoted as "X~Y" (where X and Y are arbitrary numbers), unless otherwise specified, it includes the meaning of "X or more but less than Y," as well as the meaning of "preferably greater than X" or "preferably less than Y." Additionally, when denoted as "X or more" (where X is any number), unless otherwise specified, it includes the meaning of "preferably greater than X," and when denoted as "Y or less" (where Y is any number), unless otherwise specified, it also includes the meaning of "preferably less than Y."
[0084] The above describes the embodiments of the present invention, but the present invention is not limited to any of the above embodiments and can be modified in various ways within the scope of the present invention. Example
[0085] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples.
[0086] The measurement and evaluation methods in this embodiment are as follows.
[0087] (Shrinkage rate of resin film) The resin film was cut into 12cm × 12cm pieces to prepare samples. Markings were drawn 1cm inward from the outer perimeter of the sample along the MD and CD directions, and the distance between the marks was measured using calipers. The samples were then heat-treated at 180°C for 5 minutes. After heat treatment, the distance between the marks in the MD and CD directions was measured again using calipers. For each direction in the MD and CD directions, the difference between the initial and post-heat-treatment mark distances was divided by the initial mark distance, and this value was taken as the shrinkage rate (percentage). The shrinkage rate difference (A - B)% was calculated based on the obtained shrinkage rate (A%) in the MD direction and the shrinkage rate (B%) in the CD direction.
[0088] (Constructability evaluation of window film) The release liner of the window film prepared in the examples and comparative examples was attached and temporarily affixed to the windshield of a typical passenger vehicle that had been sprayed with a construction fluid (a 0.1% aqueous solution of neutral detergent). At this time, the MD direction of the resin film was aligned with the width direction of the windshield. Then, using a heat gun, the window film was contracted while following the curved surface of the windshield, thereby attaching the window film to the windshield. The operability of following the window film was evaluated using the following criteria. A: It can be followed very easily. B: Can be easily followed C: Although it takes time, it is worth following. F: Unable to follow
[0089] (Evaluation of the transparency of window film) The release liner was peeled off from the window film prepared in the examples and comparative examples, and the exposed adhesive layer was attached to a float glass plate with a thickness of 3 mm. According to JIS S3107, the transmittance of the window film was measured by irradiating it with light in the wavelength range of 300–2500 nm using a UV-Vis-NIR spectrophotometer (manufactured by Shimadzu Corporation, UV-3600). Based on the measurement results, the transmittance (visible light transmittance) in the wavelength range of 380–780 nm was calculated. Based on the calculated visible light transmittance, the transparency was evaluated using the following criteria. A: Visible light transmittance is over 80%. F: Visible light transmittance is less than 80%.
[0090] (Evaluation of the thermal insulation properties of window film) In the light transmittance measurement for the transparency evaluation described above, light transmittance within the wavelength range of 780–2500 nm was taken at 5 nm intervals. The taken values were averaged, and the resulting value was taken as the near-infrared transmittance. Based on the calculated near-infrared transmittance, the heat insulation performance was evaluated using the following criteria. A: Near-infrared transmittance is below 20%. F: Near-infrared transmittance greater than 20%
[0091] (Evaluation of shrinkage wrinkles during window film manufacturing) When the composition for forming a hard coating applied to a resin film is cured by ultraviolet irradiation, the strength of the wavy wrinkles generated in the CD direction of the resin film is evaluated by visual inspection and using the following criteria. A: Completely wrinkle-free and in good appearance. B: Almost wrinkle-free and with a good appearance C: Although slight wrinkles are produced during curing, no wrinkles were observed after the window film was applied to the front window in the above workability evaluation. F: Strong wrinkles are produced during curing; in the above workability evaluation, wrinkles can still be observed after being applied to the front window.
[0092] (Example 1) 1. A composition for forming a hard coating As a coating liquid, a hard coating forming composition (manufactured by Mitsubishi Materials Corporation) is prepared, comprising an acrylate compound and a photopolymerization initiator, and indium tin oxide particles (c1) as an infrared absorber (c) and a urethane acrylate resin as an active energy radiation-curable oligomer. In 100% by mass of the hard coating forming composition, 60% by mass of the infrared absorber is contained.
[0093] 2. Manufacturing of window film As the resin film, a biaxially stretched polyethylene terephthalate (PET) film (manufactured by Mitsubishi Chemical Corporation) with a thickness of 25 μm was prepared. The coating solution of the prepared hard coating forming composition was applied to one main surface of the PET film by gravure coating, and heated at 70°C for 1 minute to thoroughly remove the diluent. Next, under a nitrogen atmosphere, the hard coating forming composition was cured by irradiating with ultraviolet light using an ultraviolet irradiation device (manufactured by GS Yuasa International Ltd., product name "Nitrogen-Purge Small Conveyor Belt UV Irradiation Device CSN2-40") under the following conditions, forming a hard coating (forming weight per unit area: 5 g / m²). 2 This process yields a PET film with a hard coating. [Ultraviolet radiation conditions] • Light source: High-pressure mercury lamp • Bulb wattage: 1.4kW • Conveyor belt speed: 10m / min Illuminance: 250mW / cm² 2 • Light intensity: 100 mJ / cm 2
[0094] Next, the acrylic adhesive composition was applied to the release-treated side of a release sheet (manufactured by LINTEC Corporation, product name "SP-PET381031") that had undergone single-sided release treatment with a silicone-based release agent, using a molding process. After coating, the film was heated at 90°C for 1 minute to completely remove the diluent, forming an adhesive layer (weight per unit area: 10 g / m²). 2 A release sheet and an adhesive layer are obtained. The adhesive layer of this laminate is then bonded to the main surface of the PET film with a hard coating, on the side without the hard coating, in a contact manner to obtain a window film.
[0095] (Example 2) The resin film of Example 1 was replaced with a 25 μm thick biaxially stretched polyethylene terephthalate (PET) film (manufactured by Mitsubishi Chemical Corporation) with different stretching conditions during manufacturing than that of Example 1. Otherwise, the window film was obtained in the same manner as in Example 1.
[0096] (Example 3) The resin film of Example 1 was replaced with a 25 μm thick biaxially stretched polyethylene terephthalate (PET) film (manufactured by Mitsubishi Chemical Corporation) with different stretching conditions during manufacturing than that of Example 1. Otherwise, the window film was obtained in the same manner as in Example 1.
[0097] (Example 4) The resin film of Example 1 was replaced with a biaxially stretched polyethylene terephthalate (PET) film (manufactured by Mitsubishi Chemical Corporation) with a thickness of 100 μm, and the window film was otherwise obtained in the same manner as in Example 1.
[0098] (Comparative Example 1) The resin film of Example 1 was replaced with a 25 μm thick biaxially stretched polyethylene terephthalate (PET) film (manufactured by Mitsubishi Chemical Corporation) with different stretching conditions during manufacturing than that of Example 1. Otherwise, the window film was obtained in the same manner as in Example 1.
[0099] (Comparative Example 2) The resin film of Example 1 was changed to a biaxially stretched polyethylene terephthalate (PET) film (manufactured by Mitsubishi Chemical Corporation) with a thickness of 25 μm, with different stretching conditions during manufacturing than that of Example 1. The hard coating forming composition of Example 1 was changed to a hard coating forming composition containing 40% by mass of tungsten oxide cesium particles (manufactured by Sumitomo Metal Mining Co., Ltd., product name "YMF-02AS") (c2) as an infrared absorber (c). Otherwise, the window film was obtained by the same method as in Example 1.
[0100] (Comparative Example 3) The resin film of Example 1 was changed to a biaxially stretched polyethylene terephthalate (PET) film (manufactured by Mitsubishi Chemical Corporation) with a thickness of 25 μm, with different stretching conditions during manufacturing than that of Example 1. The hard coating forming composition of Example 1 was changed to a hard coating forming composition containing 40% by mass of antimony tin oxide particles (manufactured by Sumitomo Metal Mining Co., Ltd.) (c3) as an infrared absorber (c). Otherwise, the window film was obtained by the same method as in Example 1.
[0101] The window films prepared in the Examples and Comparative Examples (Examples 1 to 4 and Comparative Examples 1 to 3) were subjected to the above-described measurements and evaluations. The results are shown in Table 1.
[0102] [Table 1]
[0103] Table 1 confirms that the window film of the embodiment has excellent workability and can suppress the generation of shrinkage wrinkles during manufacturing, as well as excellent heat insulation. Industrial applicability
[0104] The window film of the present invention can be applied to and suitably used on windows of moving bodies such as automobiles and buildings. It is particularly suitable for the front windows of automobiles with large areas and large curvatures. Explanation of reference numerals in the attached figures
[0105] 1: Window film; 10: Resin film; 11: Hard coating; 12: Adhesive layer.
Claims
1. A window film having a resin film and a hard coating disposed on a main surface of the resin film, wherein, For the resin film after heating and holding at 180°C for 5 minutes, if the shrinkage rate in the MD direction before and after heating is set as A% and the shrinkage rate in the CD direction before and after heating is set as B%, then A-B is 0.4% or more. The hard coating contains indium tin oxide.
2. The window film according to claim 1, wherein, The shrinkage rate in the MD direction is 0.75% or higher.
3. The window film according to claim 1 or 2, wherein, The visible light transmittance of the window film is over 80%.
4. The window film according to claim 1 or 2, wherein, The near-infrared transmittance of the window film is less than 20%.
5. The window film according to claim 1 or 2, wherein, The window film is used as the front window of the moving body.
6. A method for manufacturing a front window with a window film, comprising the following steps: attaching the window film of claim 5 to the front window in such a manner that the MD direction of the resin film is aligned with the long side direction of the front window.
Citation Information
Patent Citations
Window film
JP2019171781A